Upacara Saur Matua : Konsep ”Kematian Ideal” Pada Masyarakat Batak (Studi Etnoarkeologi) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2008)
AbstractSaur Matua is a funeral rites in Batak tradition for old man / woman who died, leaved children who all of them have been married, and have given grandchilds. It’s very interesting that saur matua make a controversy, because some batak people communities have said that it’s not important to save this cultural product. So this writing want to observate how useful saur matua based on its local genius since the past untill now.